The 𝘪𝘯 𝘷𝘪𝘵𝘳𝘰 effects of 𝘔𝘰𝘳𝘪𝘯𝘨𝘢 𝘰𝘭𝘦𝘪𝘧𝘦𝘳𝘢 on chaperone-mediated autophagy in human HepG₂ liver cancer cells - Bopape, Matlola Abel (University of the Free State, 2023)
𝐈𝐧𝐭𝐫𝐨𝐝𝐮𝐜𝐭𝐢𝐨𝐧: The impact of hepatocellular carcinoma (HCC) is most significant in developing countries, including South Africa. Emerging evidence suggests that the cell survival mechanism, chaperone-mediated autophagy (CMA), promotes HCC tumour progression and chemotherapeutic drug resistance. Current treatment approach for HCC is guided by the Barcelona Clinic Liver Treatment Strategy (BCLTS), which recommends different treatment approaches depending on the level of tumour progression. Despite their efficacy, currently available chemotherapeutic options have numerous limitations such acquired resistance, recurrence, and hypertension. To address these limitations, phytochemical extracts are increasingly being investigated for the anti-cancer potential. The phytochemical extracts of the medicinal plant, Moringa oleifera (MO) have been shown to induce apoptosis of HCC cells. MO leaves have the greatest abundance of phytochemicals displaying anticancer potential. Investigating the interplay between all-trans-retinoic acid (ATRA), a potential inhibitor of CMA, and MO regarding their effects on CMA holds potential in identifying adjuvant therapeutic approaches for treatment modalities for HCC. 𝗔𝗶𝗺: This study aimed to investigate the 𝘪𝘯 𝘷𝘪𝘵𝘳𝘰 effects of MO aqueous leaf extract on CMA activity in human HepG₂ cancer cells. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀: HepG₂ cells were cultured and exposed to MO and ATRA for 24 hours. Thereafter, a cell viability assay was performed and an inhibition concentration 50 (IC50) was determined which was used for all subsequent experiments. The cells were allocated to three treatment groups: MO, ATRA and a combination group of MO and ATRA. A Caspase-Glo™ cell death assay and western blot analysis were also conducted to evaluate changes in lysosome-associated membrane protein type 2A (LAMP2A) and hexokinase II (HK2) protein expression levels. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀: The cell viability assay results displayed a concentration-dependent decline in reductive capacity following MO and ATRA exposures. An IC₅₀ of 1415 μM (ATRA) and 2198 μg/mL (MO) were observed. The cell death assay revealed decreased caspase-9 activity following the respective treatment exposures. There was a corresponding decline in caspase-3/7 activity following respective treatment exposures, except for MO, where an increase in caspase-3/7 activity was observed. Western blot analysis showed a decline in the expression of LAMP2A and a corresponding increase in the expression of the CMA cargo protein HK2. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻: The results revealed that MO and ATRA could inhibit the growth and proliferation of HCC cells, offering a promising adjuvant therapeutic approach against HCC. Further investigation into these compounds and their underlying mechanisms of action may contribute to developing novel treatment modalities for HCC.
Dissertation (MMed.Sc.((Physiology))--University of the Free State, 2023
Keywords: All-trans-retinoic acid; Apoptosis; Cancer therapeutics; Chaperone-mediated autophagy; Hepatocellular carcinoma; HepG₂ cancer cells; 𝘔𝘰𝘳𝘪𝘯𝘨𝘢 𝘰𝘭𝘦𝘪𝘧𝘦𝘳𝘢